2010
DOI: 10.1089/bfm.2009.0083
|View full text |Cite
|
Sign up to set email alerts
|

Do Breastfeeding Intentions of Pregnant Inner-City Teens and Adult Women Differ?

Abstract: In a population at high risk for choosing not to breastfeed, we found no significant explanatory effect of age on breastfeeding intention, implying that an inclusive targeted breastfeeding intervention program may be effective for both teens and non-teens in a low-income inner-city population. We also found that the support of the father of the baby significantly influenced breastfeeding intent among our participants, suggesting that paternal involvement will be integral to the success of breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
2
13

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 39 publications
3
35
2
13
Order By: Relevance
“…18 Lastly, paternal involvement appears integral to the success of breastfeeding. 19 In our study the independent predictors of breastfeeding at discharge were maternal older age and paradoxically, lower parity, but not ethnicity. In a 2000-2002 study of inner-city women in Philadelphia, Lee et al 20 found a higher intention to breastfeed among African American compared with whites.…”
mentioning
confidence: 43%
“…18 Lastly, paternal involvement appears integral to the success of breastfeeding. 19 In our study the independent predictors of breastfeeding at discharge were maternal older age and paradoxically, lower parity, but not ethnicity. In a 2000-2002 study of inner-city women in Philadelphia, Lee et al 20 found a higher intention to breastfeed among African American compared with whites.…”
mentioning
confidence: 43%
“…The parallels between mothers planning formula feeding in the study by Freed et al 30 and mothers planning mixed feeding in the current study, coupled with the well-documented relationship between paternal support and the decision to breastfeed, suggest perceived negative paternal attitudes may be a factor in a woman's decision to mix feed her infant. 12 …”
Section: Discussionmentioning
confidence: 99%
“…10 Prenatal intentions are among the strongest predictors of breastfeeding duration and intensity. 11,12 Several authors have assessed predictors of maternal intention to breastfeed [13][14][15][16][17][18] -which for women of color often includes concerns about breastfeeding in public 19 -but few have measured modifiable predictors of intention to breastfeed exclusively. Provider education interventions during residency training significantly increased exclusive breastfeeding rates, although neither hospital staff training 21 nor postpartum nurse phone support was effective in doing so.…”
mentioning
confidence: 99%